Perturbed Parabolic Equation on a Riemannian Manifold - Bondarenko, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We construct a fundamental solution of an equation with perturbed diffusion operator on a manifold of nonnegative curvature.